PP.03.14: THE OPTIMAL NIGHTTIME HOME BLOOD PRESSURE MONITORING SCHEDULE. (June 2015) - Kollias, A.; Agaliotis, G.; Andreadis, E.; Achimastos, A.; Stergiou, G.S.
Abstract : Objective: Modern technology allows the evaluation of nighttime blood pressure with low-cost self-home blood pressure (HBP) monitors. This study assessed the optimal number of nighttime HBP measurements in terms of agreement with nighttime ambulatory (ABP) monitoring and prediction of target-organ damage. Design and method: Untreated hypertensives were evaluated with 24-hour ABP (20 min intervals) and HBP monitoring during daytime (6 days, duplicate morning and evening measurements) and nighttime (automated monitoring, 3 nights, 3 hourly measurements/night). Target-organ damage was assessed by echocardiographic left ventricular mass index (LVMI), carotid intima-media thickness (cIMT), urine albumin excretion (UAE) and ankle-brachial index (ABI). Results: 94 subjects with complete HBP monitoring (3-nights; 9 readings) were analyzed (mean age 51.8 ± 11.1 years, men 57%, diabetics 5%). By averaging an increasing number of nighttime HBP readings, there was a consistent trend towards stronger association of nighttime systolic HBP with (i) nighttime ABP and (ii) target-organ damage indices, with highest coefficients observed when averaging 4 or more readings (Table). The same was the case for the associations of nighttime diastolic HBP with ABP, whereas the number of readings had no impact on the associations of diastolic nighttime HBP with ABI (Table). The diagnostic agreement between HBP and ABP in detecting non-dippers was slightly improved by averaging 4 or more readings (1 reading: agreement 81%, kappa 0.37; 4 readings: 88%, 0.49; 9 readings: 84%, 0.40). Conclusions: At least 4 readings appear to be required for optimal nighttime HBP evaluation, in terms of association with nighttime ABP and target-organ damage. Figure. No caption available.